PENGELOLAAN SAMPAH PLASTIK DI SALATIGA: Praktik, dan tantangan - Berliana Anggun Septiani; Dian Mita Arianie; Via Fide Aditya Andi Risman; Widhi Handayani; Istiarsi Saptuti Sri Kawuryan (School of Postgraduate Studies, Diponegoro Univer, 2019)
The increase of solid waste production is a general problem in municipality, particularly of plastic waste. The durability, light-weight, anticorrosiveness, and inexpensiveness properties of plastic make it favorable to be used in daily life, including in Salatiga. However, plastic is one of some non-biodegradable materials that could lead to soil and water pollution as it contains toxic compounds such as aromatic hydrocarbons, phthalates, and organochlorine. Various studies in municipal solid waste management have been conducted. While those studies often applied various approaches separately, researches in regard to the role of stakeholders in municipal solid waste management are very limited. This study aims to explain the plastic waste management in Salatiga based on the role of the corresponding stakeholders. This qualitative study shows that there are four stakeholders who were involved in municipal plastic waste management in Salatiga. They were the households who generate wastes, the scavengers who sorts the wastes, Bank Sampah and collectors who have the same role in order to collect the wastes and treat the plastic wastes through reusing or recycling processes, and the government. Currently, efforts in waste treatment in Salatiga are focused on the system of collecting-tranferring-disposal mode, waste treatment by reuse and recycle processing, and landfilling. Reducing plastic consumption must take into account the sociocultural aspect and environmental awareness, as the people still interested to use plastic instead of using other materials in substitution. Finally, the role of government is central to educate the community in term of sorting activities and reducing waste production, build the capacity of Bank Sampah, and manage the role of scavengers and collectors. Other alternatives include creating synergy between the collectors and Bank Sampah, as well as ensuring final treatment of the unprocessed wastes disposed by collectors and Bank Sampah.